Beneath a scarlet sky a novel - Sullivan, Mark T. (Seattle : Lake Union Publishing, 2017)
In 1940s Italy, teenager Pino Lella joins an underground railroad helping Jews escape over the Alps and falls for a beautiful widow, he also becomes the personal driver of one of the Third Reich's most powerful commanders.
Each Book Group Kit, contained in a canvas bag, includes 12 copies of the book and one copy of a notebook containing book reviews, discussion questions, author information, a bibliography of the titles in the Book Group Kit collection, bibliographies of books and websites on book groups and enhancements (articles, maps or pictures) to help understand the book.
Keywords: Lella, Giuseppe, -- 1926- -- Fiction; World War, 1939-1945 -- Italy -- Fiction; Italy -- History -- German occupation, 1943-1945 -- Fiction; Germany -- History -- 1933-1945 -- Fiction; Historical fiction; Biographical fiction; War fiction